2019
DOI: 10.14393/bj-v35n1a2019-41605
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma species diversity in rhizosphere soils and potential antagonism with Fusarium oxysporum

Abstract: In this study six different Trichoderma species were isolated form rhizosphere soils of paddy, banana, oil palm, rubber, vegetables and grass land soils. The species are T. harziaum, T. viride, T. koningii, T. asperrelum, and T. parareesei. The morphological study as pigmentation, colony growth and anatomical studies such as, conidiation appearances, size of conidia, conidiophores branching pattern, shapes of phialides, absent or present of chlamydiophores were carried out to identify the species of Trichoderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
3
3
0
Order By: Relevance
“…During the dual culture assay, the maximum antagonistic efficiency recorded was 93.57% from the TD7 strain, followed by 90.12% by TD1, and 89.45% by TD5. This finding is consistent with those of Naher et al [ 17 ], who isolated 16 Trichoderma isolates, of which T . parareesei strain TPE7, T .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…During the dual culture assay, the maximum antagonistic efficiency recorded was 93.57% from the TD7 strain, followed by 90.12% by TD1, and 89.45% by TD5. This finding is consistent with those of Naher et al [ 17 ], who isolated 16 Trichoderma isolates, of which T . parareesei strain TPE7, T .…”
Section: Discussionsupporting
confidence: 93%
“…To alleviate the effect of chemicals (e.g., fungicides), it is important to develop economically safe, long-lasting, and effective biocontrol methods for the control of plant diseases. Trichoderma species are one excellent model that has been used as effective soil biocontrol agents with significant antagonistic potential against a wide range of fungal phytopathogens [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation might probably be attributed to different factors that could be either intrinsic (nature of the fungi) or extrinsic (media, temperature, light, and humidity). Similar to the current study, other previous studies indicated the presence of differences in morphological and cultural features (fast growth, colony color, mycelial growth habit, and colony edge) as typical characteristics of different Trichoderma isolates and as preliminary differentiating criteria(Anwer et al, 2020;Naher et al, 2019).…”
supporting
confidence: 88%
“…Although many Trichoderma species are regarded as generalistic cosmopolitans (1), the majority of specialized ecological behaviors observed in this species is rooted in their fundamental nature as mycoparasites (1). T. parareesei is thus known to exert aggressive mycoparasitism and antagonistic action against various fungi, including phytopathogens such as Fusarium oxysporum (2), Rhizoctonia solani (2), and Botrytis cinerea (3,4).…”
Section: Introductionmentioning
confidence: 99%